Tren dan Dinamika Publikasi Ilmiah dalam Bidang Perpustakaan dan Informasi di Indonesia: Analisis Bibliometrik Tahun 2020-2024 - Ramadani, M. Rifki; Ramadhan, Muhammad Basith; Riyadi, Ahmad; Saputra, Muhamad Rendy; Ghani, M. ABD; Ilmi, Miftahul (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2025)
This study aims to map the trends and dynamics of scientific publications in the field of libraries and information in Indonesia during the period 2020–2024. Data were obtained using Publish or Perish software with Google Scholar sources, and analyzed using a quantitative descriptive approach through bibliometric methods. A total of 288 articles were analyzed using Mendeley and VOSviewer software to identify publication patterns, annual distributions, and relationships between keywords through co-word analysis. The results showed a significant increase in publications in 2023, which marked a surge in interest in studies in the field of libraries and information. Visualization with VOSviewer groups research topics into several dominant clusters, including library digitization, transformation of the role of librarians, collection management, and information services. Overlay visualization indicates that the old theme that remains relevant is the role of librarians, while the topics that have developed recently are information services and digital libraries. These findings provide a comprehensive picture of the direction of scientific development in the field of libraries and information in Indonesia and become a strategic foundation for further research development.